Hyptis suaveolens (L.) Poit. (Lamiaceae) a source of edible oil among tribals of Orissa, India - AMINUDDIN, R D GIRACH, AMINUDDIN (Journal of Spices and Aromatic Crops, 1993)
The tribal use of Hyptis suaveolens (Lamiaceae) as a source for edible oil purpose in cooking medium is reported for the first time from Gandhamardan hill areas of Bolan gil’ district in Orissa, India.